Hip Impingement after Anterior Inferior Iliac Spine Avulsion Fractures: A Case Report with Review of the Literature - Mark J. Lambrechts; Aaron D. Gray; Dan G. Hoernschemeyer; Sumit Kumar Gupta (Case Reports in Orthopedics)
Avulsion fractures of the anterior inferior iliac spine (AIIS) are rare injuries in adolescent athletes. We present a case of a 15-year-old male who sustained an avulsion injury to his right AIIS when kicking a soccer ball. The patient had chronic pain and extra-articular subspinal impingement leading to decreased hip flexion and rotation. The injury occurred 1.5 years prior to symptom onset, and we were the first health care providers to manage the injury. We attempted six months of nonoperative management including activity modifications and nonsteroidal anti-inflammatory (NSAID) therapy without improvement. Although this injury can often be managed nonoperatively, his symptoms required excision of the AIIS and associated heterotopic ossification. He had an excellent outcome with return to soccer and no pain at his final follow-up visit two years after surgery. Due to the limited literature guiding the surgeon’s management of AIIS avulsion injuries with associated heterotopic ossification, we provide a review of the literature detailing pre- and postoperative ranges of motion, surgical approach, fixation or excision of the avulsion fragment, and return to sport in this patient population.